Diagnostic efficacy of sepsis-screen parameters (individual and combined) compared to blood culture and clinico-etiological profile of neonatal sepsis in preterm newborns - Dr. Pratima Beck; Dr. Santosh Kumar Rathia; Dr. Sharja Phuljhele; Dr. Sharja Phuljhele (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Sepsis alone or along with other morbidity is the major contributor to mortality in both preterm and term babies accounting for more than a third of neonatal deaths in developing countries. Overall incidence of early onset sepsis (EOS) is higher in preterms and very low birth weight babies. Sepsis and related mortality is largely preventable with rational antimicrobials plus supportive therapy after timely detection of clinical sepsis, risks, complications, and with help of early screening laboratory-markers. Material and Method: This was a prospective, observational, hospitalbased study to compare the efficacy between various sepsis-screening tests & blood culture in early diagnosis of neonatal sepsis in preterms, conducted in NICU at Pt. JNM Medical College, Raipur, conducted during April 2018-September 2018. By using statistical Sample-size formula, 125 preterm neonates were enrolled. Detailed history and clinical findings were recorded on a predesigned proforma. All five sepsis-screen tests were done within 24 hours of birth or at clinical presentation before starting antibiotics, for all preterms at risk of EOS (based on neonatal/maternal risk factors>3) and/or developing clinical sepsis. Data was compiled, tabulated and analyzed using Microsoft-SPSS version20. Result: Out of 125 patients, all were preterm <37weeks by gestation (<28 week=3.2%, 28-32 weeks=52%, 32-35 weeks=33.6% and late preterm: 35-37weeks =11.2%). Birth weight wise, 15.2% were ELBW, 45.6% were VLBW, and 39.2% weighed >1500g. Out of all sepsis-suspect and at risk cases, EOS risk factors (>/=3 of maternal plus neonatal risks) was present in 47.2%, while EOS was suspected at admission in 83.2% cases on clinical ground. Overall sepsis screening was positive (>=2 parameters) in 40% of all subjects [24% having only 2, 10.4% having 3 and 5.6% having 4 tests positive], though >50%cases had single test positive (considered screen-ve). Although >88%cases developed clinical sepsis (EOS+LOS), only 40% were detected by screen positive (as probable sepsis), and 35.2% were blood culture positive (proven sepsis). Conclusion: The combinations of sepsis makers yielded better diagnostic results than single tests and proved to be a valuable aid for early diagnosis of neonatal sepsis in preterms along with blood culturesensitivity.